Mycobacterial Infection of the Gallbladder Masquerading as Gallbladder Cancer with a False Positive Pet Scan. (14th March 2013) - Majid, Adeeb; Raju, Ravish Sanghi; Trochsler, Markus; Kanhere, Harsh A.; Maddern, Guy J.
Abstract : Isolated mycobacterial infection of gall bladder is an extremely rare entity. Only anecdotal reports are evident in the literature. A preoperative diagnosis of mycobacterial infection of gallbladder is therefore very difficult. The case of a 72-year-old male who underwent surgery for suspected gallbladder cancer is presented. The diagnosis of cancer was based on radiological findings and an abnormal uptake of fluorine-18-fluoro-2-deoxy-D-glucose (FDG) on positron emission tomography (PET) scan whilst being followed up for colorectal cancer. He underwent cholecystectomy and gallbladder bed resection. Histopathology was consistent with mycobacterial infection of the gallbladder.